Actor networks in specialized accounting inspection: an analysis in the light of the Actor-Network Theory - Murro, Eduardo Vinícius Bassi; Beuren, Ilse Maria (Review of Business Management, 2016)
Purpose – This study investigated the configuration of human and non-human actor networks that are formed in the process of specialized accounting inspection from the Actor-Network Theory perspective. Design/methodology/approach – The population of the survey comprised 593 accounting experts registered in Expert Associations from the Brazilian states of Minas Gerais, Paraná, Rio de Janeiro, Rio Grande do Sul and São Paulo, and the sample is made up of 102 valid questionnaires. Five judges and five accounting experts from Curitiba (state of Paraná) were also interviewed. Through Structural Equation Modeling, the translation process indicated statistical significance, except in the relationship between human accounting actors, nonhuman actors and problematization. Findings – Based on this research, we concluded that the establishment of networks in the field of specialized accounting inspection depends on numerous translations between agents, since they have an impact on the performance of activities and the stabilization of relationships. The quality of the expert report and technical report and the competence of accounting experts were pointed out as performance indicators. Accounting experts and accounting experts assistant’s experience, the period of experience and the relationship with judges were identified as drivers of stable and lasting relationships between specialized accounting inspection actors. Originality/value – The study is relevant given the lack of research involving the Actor-Network Theory and accounting, particularly Accounting Inspection, both nationally and internationally. Therefore, contribute to investigate how the actors interact, create and modify relationships, through the perception of accountants and judges.